Range correlation and I/Q performance benefits in single-chip silicon Doppler radars for noncontact cardiopulmonary monitoring - Droitcour, A.D.; Boric-Lubecke, O.; Lubecke, V.M.; Lin, J.; Kovacs, G.T.A. (IEEE transactions on microwave theory and techniques, 2004)
Direct-conversion microwave Doppler-radar transceivers have been fully integrated in 0.25-/spl mu/m silicon CMOS and BiCMOS technologies. These chips, operating at 1.6 and 2.4 GHz, have detected movement due to heartbeat and respiration 50 cm from the subject, which may be useful in infant and adult apnea monitoring. The range-correlation effect on residual phase noise is a critical factor when detecting small phase fluctuations with a high-phase-noise on-chip oscillator. Phase-noise reduction due to range correlation was experimentally evaluated, and the measured residual phase noise was within 5 dB of predicted values on average. In a direct-conversion receiver, the phase relationship between the received signal and the local oscillator has a significant effect on the demodulation sensitivity, and the null points can be avoided with a quadrature (I/Q) receiver. In this paper, measurements that highlight the performance benefits of an I/Q receiver are presented. While the accuracy of the heart rate measured with the single-channel chip ranges from 40% to 100%, depending on positioning, the quadrature chip accuracy is always better than 80%.